Pengaruh Inflasi dan GDP terhadap Tingkat Kesehatan Bank Syariah dengan Size sebagai Pembeda - Rohmah, Nisa Aulia; Darmawan, Darmawan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The research aims to determine the impact of Inflation and Gross Domestic Product (GDP) on the health level of Islamic Banks in Indonesia from 2014 to 2020 with size as the differentiator. The population in this study is 14 Banking Companies from 2014 to 2020 registered with the Financial Services Authority (OJK), and using a purposive sampling technique, 14 banks were select as the research sample. The analysis method used is the panel data analysis method using Eviews 12. The health level of the Islamic Commercial Bank is calculate using the RGEC method is measured using Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Assets (ROA), and Capital Adequacy Ratio (CAR). The result of this study shows that inflation and GDP do not have a significant effect on NPF, FDR, and ROA. Meanwhile, inflation and GDP have a significant effect on the CAR Small size.